The dynamic relationship between the federal funds rate and the Treasury bill rate: An empirical investigation - Sarno, Lucio; Thornton, Daniel L. (Journal of Banking & Finance, 2003)
This article examines the dynamic relationship between two key US money market interest rates––the federal funds rate (FF) and the 3-month Treasury bill rate. Using daily data over the period from 1974 to 1999, we find a long-run relationship between these two rates that is remarkably stable across monetary policy regimes of interest rate and monetary aggregate targeting. Employing a nonlinear asymmetric vector equilibrium correction model, which is novel in this context, we find that most of the adjustment toward the long-run equilibrium occurs through the FF. In turn, there is strong evidence for the existence of significant asymmetries and nonlinearities in interest rate dynamics that have implications for the conventional view of interest rate behavior.